Influence of thermal stabilization treatment on the subsequent microstructure development during directional solidification of a Ti–46Al–5Nb alloy. (August 2015) - Zhang, Liwei; Lin, Junpin; He, Jianping; Yin, Jia; Ding, Xianfei
Abstract: Directional solidification (DS) experiments with thermal stabilization (TS) treatments were performed on Ti–46Al–5Nb (at.%) alloys in a Bridgman-type furnace using a quenching technology. Influence of the TS treatment on mushy zone and directional growth afterwards were investigated. The results show that the length of the mushy zone decreases but the β dendrite spacing in directional growth significantly increases with increasing TS time. During the DS process, β dendrite spacing is more homogeneous and its growth direction is more inclined to parallel to the axial direction with increase of the TS time. Al solute concentration in the mushy zone in a steady-state is always lower than that in original as-cast alloys. The mushy zone with the columnar β and α grains is easily produced after TS treatment on the alloys with microstructures of the directional dendrite segregation morphology before DS starting. TS treatment results in the redistribute of solute Al thus changes the phase constituent in the mushy zone. An appropriate TS is necessary to produce the L + β + α region in the mushy zone, which is of great benefit to control DS microstructures of TiAl peritectic alloys. Highlights: Length of the mushy zone decreases with increasing thermal stabilization (TS) time. β dendrite spacing in directional growth increases with increasing TS time. TS results in solute redistribute thus changes the phase constituent in mushy zone. An appropriate TS is necessary to produce the L + β+ α region in mushy zone.